2021
DOI: 10.3390/toxics9060126
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Aging Affect Glyphosate Toxicity and Fatty Acid Composition in Allonychiurus kimi (Lee) (Collembola)

Abstract: Glyphosate is the most used herbicide worldwide, but enormous use of glyphosate has raised concerned about its environmental loadings. Although glyphosate is considered non-toxic, toxicity data for soil non-target organisms according to temperature and aging are scarce. This study examined the toxicity of glyphosate with the temperature (20 °C and 25 °C) and aging times (0 day and 7 days) in soil using a collembolan species, Allonychiurus kimi (Lee). The degradation of glyphosate was investigated. Fatty acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…For example, the compressed soil test allows continuous monitoring of molting, number of eggs and hatchability without pretreatment during exposure periods because on the compressed soil collembolans cannot burrow in the soil (Lee, Son et al, 2019 ). Moreover, some studies suggested more sensitive biomarkers using regulating patterns of protein, composition of fatty acid, and gene expression (Lee et al, 2018 ; Nota et al, 2008 ; Wee, Lee, Kim, Son, et al, 2021 ). Although these alternative approaches and biomarkers overcome the limitations of the existing methods, it is still a laborious procedure to obtain the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the compressed soil test allows continuous monitoring of molting, number of eggs and hatchability without pretreatment during exposure periods because on the compressed soil collembolans cannot burrow in the soil (Lee, Son et al, 2019 ). Moreover, some studies suggested more sensitive biomarkers using regulating patterns of protein, composition of fatty acid, and gene expression (Lee et al, 2018 ; Nota et al, 2008 ; Wee, Lee, Kim, Son, et al, 2021 ). Although these alternative approaches and biomarkers overcome the limitations of the existing methods, it is still a laborious procedure to obtain the results.…”
Section: Discussionmentioning
confidence: 99%
“…Then, this collembolan population has been maintained at the Ecology & Toxicology Laboratory, Korea University, Seoul, South Korea (accession number KUETCOLC001) for approximately 25 years (Lee, Lee et al, 2021 ). The A. kimi colony was maintained in a plastic Petri dish (90 mm × 15 mm (diameter × height) (D × H)) filled with 0.5 cm deep substrate comprise of plaster of Paris, activated charcoal, and distilled water at a ratio of 4:1:4 by volume at 20 ± 1°C with continuous darkness (Wee, Lee, Kim, Son et al, 2021 ). Distilled water was added periodically, and the plastic Petri dishes were aerated weekly to maintain the fresh condition of the substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature-responsive polymeric materials are substances that exhibit changes in their physical or chemical properties in response to variations in the external temperature. , The most representative property of such materials is LCST; when the homogeneous polymer starts phase separation at a high temperature, the lowest temperature of the phase separation curve on the concentration–temperature diagram is considered the critical solution temperature. Specific temperature-sensitive polymeric materials experience reduced solubility, leading to precipitation or phase separation.…”
Section: Stimulus-responsive Controlled Releasementioning
confidence: 99%